Oral or intravenous midazolam? Sedation, pain and satisfaction among patients undergoing gastroscopy in Cusco - Cuevas Cisneros, Jimy Williams (2025)
Objective: To compare the levels of sedation, pain and satisfaction among patients who received oral vs. intravenous midazolam for gastroscopy. Materials and methods: A quantitative, correlational, observational, analytical and cross-sectional study was conducted. The population consisted of patients from Cusco (3,400 m a.s.l.) treated at Hospital Regional del Cusco. The study analyzed the type of sedation (oral vs. intravenous) and midazolam dosage, as well as the level of sedation using the Ramsay Sedation Scale, perceived pain and patient satisfaction. Student’s t test and Mann-Whitney U test were used to assess differences according to the route of administration. Results: A total of 150 patients participated in the study, 71 % of whom were male, with a mean age 55.5 years. Midazolam was administered orally (55 %) and intravenously (45 %), with a mean dose of 5.47 mg. Forty-four percent of patients reported experiencing anterograde amnesia. Patient satisfaction was evaluated across several dimensions, highlighting a general preference for waiting times and the care received during the procedure. Additionally, 63 % of the patients expressed willingness to repeat the procedure at the same hospital and 79 % with the same physician. In the analysis of Student’s t test and Mann-Whitney U test, significant differences in levels of sedation, pain and satisfaction were sought between the routes of midazolam administration. The results indicate no significant differences between oral and intravenous midazolam, except for discomfort during the gastroscopy, where marginal statistical significance was observed. These findings suggest that both oral and intravenous administration of midazolam for gastroscopy have similar effects on sedation, pain and patient satisfaction. Conclusions: The study suggests that oral midazolam may be a viable and potentially preferable alternative to intravenous midazolam for sedation during gastroscopy, offering an optimal balance between efficacy and patient satisfaction.